Étude de l'hivernité urbaine, analyse d'un récit de construction identitaire montréalais - Myriam, Guillemette (Université du Québec à Montréal, 2020)
Keywords: Carnaval; Climat; Espace souterrain

The High Ground: Mansions, Mythology, and the Mountain - Macleod, Roderick (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Paysages; Quartiers

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

Le bois urbain du grand Montréal, un espace changeant et ambigu. - Sénécal, Gilles Gaston (Cap-aux-Diamants, 2023)
issued: 2023-22-00
Keywords: Mont-Royal (parc); Parcs

Recherche ou lobbyisme ? L’Institut économique de Montréal et le réchauffement climatique depuis 1999 - Lamy, Guillaume (Politique et Sociétés, 2022)
Keywords: Climat; Libéralisme

Expertise, Local Knowledge, and the Construction of the Automobile as an Environmental Risk in Montreal, 1960s-70s - Poirier, Valérie (Canadian Historical Review, 2020)
Number: 3
Keywords: Automobile; Groupes populaires; Pollution

Du biogaz en héritage. Mobilisations autour d’un « gisement » d’énergie dans une décharge urbaine (Montréal, 1986– 2009) - Marrec, Anaël (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Groupes populaires; Pollution

Cohabitation, exploitation et nuisances à Montréal et à La Nouvelle-Orléans : les relations entre les populations urbaines et animales, 1840-1890 - Gagnon, Benjamin (Université du Québec à Trois-Rivières, 2020)
Keywords: Alimentation; Faune

« Il s'en tuë jusques dans les jardins de Québec ». La place des animaux sauvages dans la ville (Québec et Montréal, 1663-1763) - Riguelle, William (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Alimentation; Faune